Quietly in the Orchard: about one element in Chekhov's last play - Доманский, Юрий (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2011)
The paper addresses one element of Chekhov’s play entitled The Cherry Orchard: a note in which the word “silently” is repeated twice. It is proved that the semantics of the character in Chekhov’s plays can be formed on the basis of confrontation words and events.